Injectable Thermosensitive Iodine‐Loaded Starch‐g‐poly(N‐isopropylacrylamide) Hydrogel for Cancer Photothermal Therapy and Anti‐Infection. Issue 18 (9th May 2022) - Fan, Man; Li, Mengyao; Wang, Xiao; Liao, Yonggui; Wang, Hong; Rao, Jingyi; Yang, Yajiang; Wang, Qin
Abstract: Although photothermal therapy (PTT) can effectively eliminate tumors, the normal tissues near tumors are inevitably damaged by heat and infected by bacteria, which greatly limits the therapeutic effect. In this work, an injectable thermosensitive hydrogel based on iodine‐loaded starch‐ g ‐poly( N ‐isopropylacrylamide) (PNSI) is developed to overcome this problem. FTIR, 1 H NMR, and UV–vis spectra confirm the graft copolymerization of poly( N ‐isopropylacrylamide) with starch and the formation of "iodine−starch" complex. Transmission electron microscope images show PNSI polymer self‐assembles into regular spherical nanogel with a size of ≈50 nm. The concentrated nanogel dispersion is a sol at room temperature and transforms to hydrogel at body temperature. Under NIR laser irradiation for 10 min, the Δ T of the nanogel dispersion approachs about 20 °C with excellent thermal stability and high cytotoxicity due to the photothermal effect of the "iodine−starch" complex. After intratumor injection, this injectable hydrogel efficiently inhibites the tumor growth under 808 nm laser irradiation. Furthermore, it can also suppress Staphylococcus aureus infection in the wound post‐PTT due to the release of iodine, which promotes wound healing. Therefore, this injectable thermosensitive "iodine−starch" composite hydrogel with advantages of good biocompatible and easy preparation possesses potential application for tumor photothermal therapy and antibacterial infection. Abstract : An injectable thermosensitive hydrogel containing iodine−starch complex integrates photothermal therapy and bactericidal effects. Such system has the advantages of simple preparation, good biosafety, and high therapeutic effect for tumor and wound healing.